Analisis Framing Pemberitaan Debat Pilpres 2024 Pada Asumsi.co dan Republika.co.id: Kajian Afiliatif dan Konstruksi Realitas Media - Faiz Maulida; M. Soebiantoro; Bowo Sugiarto (Faculty of Social and Political Sciences, Universitas Singaperbangsa Karawang, Indonesia, 2025)
This study analyzes the framing of the 2024 Presidential Election debate coverage in two media outlets, asumsi.co and republika.co.id, both with political affiliations. Asumsi.co, led by Pangeran Siahaan, also serves as the spokesperson for the Ganjar-Mahfud National Winning Team (TPN), while republika.co.id is owned by PT Mahaka Media Tbk, affiliated with Erick Thohir, a key member of the Prabowo-Gibran National Campaign Team (TKN). Using Robert N. Entman's, the results show that asumsi.co emphasizes the positive image of the Ganjar-Mahfud pair, highlighting their strong debate performance and mastery of the material, while republika.co.id offers more varied coverage, focusing on the candidates' personalities, physical gestures, and rhetoric, with a primary focus on Prabowo and Gibran, and criticism of Anies regarding political ethics. Keywords: Political affiliation, framing, mass media, presidential debate, framing analysis